Sevā as a Postcapitalist Model for Environmental and Collective Well-Being in the Postsecular Age - Michal Erlich; Ricki Levi (Religions)
This paper analyzes the Hindu concept of sevā—selfless service—as a theo-ethical practice that reconfigures the relationship between religion and economy, offering a snapshot of an Indian perspective on the convergence between postsecularism and postcapitalist discourses. Rather than being reducible to acts of charity, sevā integrates spiritual, ethical, and social dimensions that challenge the neoliberal emphasis on individual self-interest and material accumulation. Rooted in the pursuit of liberation and relational well-being, sevā frames economic and moral agency in terms of embeddedness, reciprocity, and care. To illustrate sevā’s unique attributes, the paper engages with two case studies. The first explores Mahatma Gandhi’s philosophy, where sevā is articulated through a non-anthropocentric ethic of nonviolence (ahiṃsā), obliging the reconstruction of eco-economic mechanisms and environmental responsibility. The second examines contemporary guru-bhakti communities in Delhi’s urban peripheries, where sevā functions as spiritual discipline (sādhana), a means for communal uplifting, and the expression of kalyāṇ—holistic well-being that transcends individual boundaries. In both contexts, sevā emerges as a practice that intervenes in and reshapes socio-economic life. By foregrounding sevā as a lived practice, the paper situates Indian religious traditions as a distinctive contribution to broader postcapitalist and postsecular debates. It argues that sevā offers an alternative model of personhood and ethical intentionality—one that contests dominant binaries of spiritual/material, secular/religious, and human/nature, and reimagines human flourishing through the lens of relational ontology and collective responsibility.